Anorexia nervosa - fenomen ponowoczesnej kultury i choroba systemu rodzinnego - Frąckowiak, Monika (Wydawnictwo Naukowe UAM, 2005)
The aim of this article is to present anorexia nervosa as a complex phenomenon which ought to be analyzed in macro-, mezzo- and microstructural context. Anorexia is defined in terms of “self destructive adaptation strategy” which is considered to be a reaction to specific configuration of cultural patterns and family system. The most significant factors affecting the process of forming the identity based on being an anorectic are: perfectionism and contemporary standards of beauty - as far as culture is concerned as well as dysfunctions of communication structure and lack of flexibility in role patterns - as far as family is concerned. To ilústrate the mentioned process on mezosocial level there have been presented results of content analysis of websites dealing with anorexia. As a conclusion, the author sketches the main assumptions of individual and family system psychotherapy of anorectics.
Anorexia nervosa - the phenomenon of postmodern culture and dysfunction of family system